Olive phenols efficiently inhibit the oxidation of serum albumin-bound linoleic acid and butyrylcholine esterase - Roche, Marjolaine; Dufour, Claire; Loonis, Michèle; Reist, Marianne; Carrupt, Pierre-Alain; Dangles, Olivier (Biochimica et biophysica acta, 2009)
Olive phenols are widely consumed in the Mediterranean diet and can be detected in human plasma. Here, the capacity of olive phenols and plasma metabolites to inhibit lipid and protein oxidations is investigated in two plasma models. The accumulation of lipid oxidation products issued from the oxidation of linoleic acid bound to human serum albumin (HSA) by AAPH-derived peroxyl radicals is evaluated in the presence and absence of phenolic antioxidants. Phenol binding to HSA is addressed by quenching of the Trp214 fluorescence and displacement of probes (quercetin, dansylsarcosine and dansylamide). Next, the esterase activity of HSA-bound butyrylcholine esterase (BChE) is used as a marker of protein oxidative degradation. Hydroxytyrosol, oleuropein, caffeic and chlorogenic acids inhibit lipid peroxidation as well as HSA-bound BChE as efficiently as the potent flavonol quercetin. Hydroxycinnamic derivatives bind noncompetitively HSA subdomain IIA whereas no clear site could be identified for hydroxytyrosol derivatives. In both models, olive phenols and their metabolites are much more efficient inhibitors of lipid and protein oxidations compared to vitamins C and E. Low postprandial concentrations of olive phenols may help to preserve the integrity of functional proteins and delay the appearance of toxic lipid oxidation products.